Development of Practical Learning Media 5-Speed Manual Transmission - Muhammad Priya Permana; Muhamad Amiruddin; Ismail Kholid (Jurnal E-Komtek (Elektro-Komputer-Teknik), 2023)
President of the Republic of Indonesia, Joko Widodo, emphasized that currently the focus of education is to provide job skills to the younger generation. Vocational education and training will continue to be strengthened in line with the shift in development strategies from physical infrastructure development to human development. The closer the student is in working life, the better and professional educational goals are achieved. The purpose of this study is to create a 5-speed manual transmission learning media that can be used for learning. There are media test and tool use test with implementation power test and user response. The results of the test showed that media trials and tool use trials resulted in 75% feasibility. Eligibility is taken by filling the expert judgment which is more than 51%. Keywords: Learning Media, 5-speed Manual transmission, feasibility test